Wireless sensor network-based health monitoring and smart home assistance for the older adults in sports and wellness towns - Dapeng Yang; Junqi Wang; Li Huang; Tongling Wang (Frontiers in Public Health)
BackgroundIntegrating technology with rural development is essential for addressing the unique challenges faced by aging populations in rural areas. China’s national rural revitalization strategy emphasizes the importance of developing characteristic towns that focus on health and wellness demands, particularly for the older adults. However, there is a gap in the literature regarding the systematic use of technology to support the health and daily living needs of this demographic.ObjectiveThis study aims to bridge this gap by proposing a wireless sensor network (WSN)-based system that integrates health monitoring and smart home assistance, specifically tailored for older adults residents in sports and wellness towns.MethodsThe system’s design involves collecting and analyzing historical activity data and basic physiological parameters from older adults residents’ homes. The data are cleaned, combined and stored to prepare it for behavior analysis, which is vital for controlling smart home equipment. Preliminary health assessments are conducted using the collected physiological data. A hybrid network leveraging Sub-G and Wi-Fi technologies is optimized for the purposes of collecting and uploading data, based on a comparative analysis of wireless communication options.SignificanceThis study significantly contributes to the advancement of sports and wellness towns by promoting healthy aging through cutting-edge technological solutions.